Practice Field Experience Integrated In Quality Improvement of Teacher - Binti Rosyidah (EDUCATIO : Journal of Education, 2016)
Considering on the Indonesian Teacher and Lecturer Act, every Indonesian teacher needs to have a teacher certification. Indeed, it is a good opportunity as well as a challenge for every university, the which is conducting teacher training program, to have qualified graduates. As a qualified teacher, he must have four competencies concerning pedagogy, attitude, personal, and social. The question that may Arise is "How to have such competencies?" Of course, many ways can be done. However, improving the quality of teaching practicum is one of the many possibilities that can be considered. Integrated Student Community Service - Teaching Practicum (KKN-PPL) the which is combining community service and teaching practicum program itself has been developed by Yogyakarta State University (UNY) to have a better models of such teaching practicum.